Penanaman Sikap Mandiri Dan Tanggung Jawab Melalui Pembelajaran Pendidikan Kewarganegaraan Di Sekolah Dasar - Mahulae, Tiara Rosalia; Sunaryati, Titin; Sopotunida, Dea; Darmawan, Jingga Agustin Eka (Jurnal Ilmiah Wahana Pendidikan, 2023)
Citizenship education is a conscious and planned effort to foster citizens, especially the younger generation, as the next generation of the nation. Citizenship education teaches students about norms, values, and morals. By practicing the norms, values, and morals that exist within students, an attitude of independence and responsibility will be created. Planting an attitude is a process of guiding students to become fully human beings with character in the dimensions of the heart, mind, body, emotion, and will or intention. The benefit of this research is to be able to find out the effect of learning Citizenship Education on instilling an attitude of independence and responsibility in students in elementary schools. The purpose of this study was to find out whether educators can instill an attitude of independence and responsibility in their students through learning Citizenship Education in elementary schools. The method used in this research is qualitative. And the results obtained from this research are to find out how effective it is to instill an attitude of independence and responsibility in elementary school students through citizenship education.